PENGARUH PELAYANAN TERHADAP KEPUTUSAN KONSUMEN MEMINJAM DI BANK SYARIAH SIDOGIRI (STUDI PADA BANK BMT SYARIAH SIDOGIRI) - nurul a'yun (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2022)
The development of the banking and financial services industry has experienced rapid progress in recent years as a result of technological advances and deregulation policies. The existence of financial deregulation resulted in a new phenomenon that resulted in a warmer competitive climate, including competition in Islamic banking. This happens because competition in the banking world is triggered by the growth of each bank. Based on the analysis that has been carried out in this study, it can be concluded that there is a positive influence between service on consumer decisions to borrow at Bank BMT Syari'ah Sidogiri and there is a positive influence between interest rates on consumer decisions to borrow at Bank BMT Syari'ah Sidogiri